Położenie Żydów polskich podczas kampanii 1920 r. - Walicki, Jacek (Acta Universitatis Lodziensis. Folia Historica, 1995)
The Polish-Jewish conflict underwent a significant mitigation in autumn 1919 and flared up again as the result of defeats sustained in summer 1920 by the Polish army; then several anti-semitic manifestations took place on the part of several military units. Also, antisemitic agitation of the Polish right wing developed which accused the Jews of pro-Bolshevik liking. Its elements penetrated into the government propaganda as well. In August the new nourishment for sharpening of the Polish-Jewish relations became hostile accusations of the Jewish of the cooperation with the Bolsheviks. In fact, the attitude of the Bolshevik authorities towards the Jewish was unfriendly and the Red Army organized their pogroms in a few villages. In spite of this, the military authorities undertook several acts directed towards the Jewish from which the greatest shadow on the development of the Polish-Jewish relations was interning of the Jewish soldiers (including volunteers) in the camp in Jabłonna. In such atmosphere lynches on the Jews and too hostile sentencing them by martial courts took place in the front area. The number of the dead did not exceed 20 yet. Much worse was the situation in the areas where the allied units of the Whiteguards, Ukrainian and the Polish army operated. The number of the dead reached a. few hundred there. The events of summer 1920 took place in the conditions of military defeat and the threat of the political existence of the country. They took place in the situation in which one always looks for a scapegoat that could be blamed for all the misfortunes and when the accusations of spying and cooperation with the enemy had a massive character (it concerns mainly the representatives of national minorities). The role that the people of Jewish origin played in October Revolution and the relative freedom that the Jews in the Soviet Russia enjoyed, were for most people and, what must be stressed with pain, for the part of authorities as well (mainly military) an argument for recognition of the Polish Jews as an illegal element. However, the number of the dead was not very big, especially against a background of other mid-eastern European countries. The separate matter are crimes commited by Whiteguardian units; in the situation that took place in July-August 1920 their usage from the military point of view was fully justified, and the military situation did not allow for resignation from their services. In spite of that, it must be stressed that although the conditions in which the anti-Jewish incidents took place limit the burden of guilt put on the authorities and the Polish society, nevertheless, these events are undoubtedly „the black card” in the history of relations of these two nations.